TINJAUAN HADITS TENTANG KEPEMIMPINAN PEREMPUAN - Hidayatulloh, Haris (Institut Agama Islam Riyadlatul Mujahidin (IAIRM) Ngabar Ponorogo, Indonesia, 2020)
The leadership of women in the public sphere is often debated by scholars, including scholars of hadith. Based on the literature review, this article examines the quality of the hadith on women leadership. The hadith research includes the text of hadith, asbab al-wurud of hadith, takhrij al-hadith based on narrators of hadith, the contents of the hadith, and the contextualization of hadith. The findings of this study are: Bukhari, An-Nasai, At-Turmudzi, and Ahmad Ibn Hambal have narrated hadiths about the disadvantages of a society led by women. Asbab al-wurud of this hadith tells about the narration of this hadith when the Persian King was killed, then the power was held by a granddaughter of the king. The narrators of this hadith all continued from Hasan (Muhammad grandson). Based on its sanad and matan, the quality of this hadith is sahih. But there are contextual differences if this hadith is applied in Indonesia.